2022
DOI: 10.3390/ijerph19031148
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolonged Absence of Organized Training on Body Composition, Neuromuscular Performance, and Aerobic Capacity: A Study in Youth Male Soccer Players Exposed to COVID-19 Lockdown

Abstract: The aim of this study is to examine how physical performance has changed after 15 weeks (109 days) long-term absence of organized training in youth soccer players imposed by the stay at home orders. A total of sixty-eight young male soccer players from different age categories (U15, U16, U17 and U19) voluntarily participated in the prospective cohort study. Body fat percentage (BF%), counter-movement jump (CMJ), 30 m sprint, change-of-direction (COD) and yo-yo intermittent recovery test level-1 (YYIRTL-1) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(30 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…The information about detraining effects is now important because COVID-19 brought challenges regarding prolonged inactivity or low activity caused by a governmental lockdown [8]. In fact, the presence of the COVID-19 pandemic during the last two years made the entire training process in football very difficult, as the imposed restrictions and lockdowns resulted in long-term detraining effects [9]. To better understand the effects that COVID-19 lockdown has on a player's physical fitness, only a few studies have been published [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information about detraining effects is now important because COVID-19 brought challenges regarding prolonged inactivity or low activity caused by a governmental lockdown [8]. In fact, the presence of the COVID-19 pandemic during the last two years made the entire training process in football very difficult, as the imposed restrictions and lockdowns resulted in long-term detraining effects [9]. To better understand the effects that COVID-19 lockdown has on a player's physical fitness, only a few studies have been published [9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the presence of the COVID-19 pandemic during the last two years made the entire training process in football very difficult, as the imposed restrictions and lockdowns resulted in long-term detraining effects [9]. To better understand the effects that COVID-19 lockdown has on a player's physical fitness, only a few studies have been published [9][10][11][12]. However, from the available research on this topic, only two studies were conducted on youth soccer players [9,11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the linear sprint performance, 10 m and 20 m sprint times were significantly improved by 7.85% and 3.73%, respectively, after the confinement period. These findings are in contrast to the results of similar studies that also investigated the effects of the COVID-19 lockdown on sprint performance in soccer [21,23,24] and futsal [35]. More specifically, Alvurdu et al [21] reported significant decrements in 30 m sprint performance after 109 days of training cessation, whereas, similarly, Grazioli et al [23] showed that 63 days of home confinement led to a reduced 10 m and 20 m sprint performance in professional soccer players.…”
Section: Discussionmentioning
confidence: 73%
“…These findings are in contrast to the results of similar studies that also investigated the effects of the COVID-19 lockdown on sprint performance in soccer [21,23,24] and futsal [35]. More specifically, Alvurdu et al [21] reported significant decrements in 30 m sprint performance after 109 days of training cessation, whereas, similarly, Grazioli et al [23] showed that 63 days of home confinement led to a reduced 10 m and 20 m sprint performance in professional soccer players. In the study by Spyrou et al [35] the same results were observed in elite futsal players, as 70 days of reduced training impaired 10 m sprint performance.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation